Activity enhancement upon the incorporation of titanium: au@ti-sio2 core-shell nanocatalysts for the CO oxidation reaction - Sekhar, Anandakumari C. Sunil; Kottavarithottil Ziyad; Soni, Yogita; Vinod, Chathakudath P. (ChemCatChem, 2015)
The encapsulation of gold nanoparticles 8-12nm in size within a porous Ti-SiO2 shell to form a core-shell nanoarchitecture was investigated, and the catalytic activity of the resulting structure was probed. Detailed characterization of the synthesized materials shows that the core-shell morphology is lost beyond a certain amount of incorporated titanium, and results in normal gold-supported Ti-SiO2. The material has a high surface area (913m(2)g(-1)) and high porosity, both of which make it an excellent choice for catalytic applications. With the optimum amount of incorporated Ti, the core-shell catalyst shows excellent room-temperature CO oxidation activity over several cycles with retention of its morphology at higher temperatures.
Keywords: core-shell structures; gold nanoparticles; Oxidation; Ti-SiO2

Convenient route for Au@Ti-SiO2 nanocatalyst synthesis and its application for room temperature CO oxidation - Soni, Yogita; Kumar, Anumol Erumpukuthical Ashok; Nayak, Chandrani; Deepak, Francis Leonard; Vinod, C. P. (Journal of Physical Chemistry C, 2017)
Small gold nanoparticles.of size less than 5 nm encapsulated inside titanium modified silica shell have been reported. Here, a modified sol-gel method, which is a one-step process, produces Au@Ti-SiO2 nanocatalyst with a good control of titanium loading. With a titanium loading of 0.9 and 2.2 wt % in silica, unprecedented low temperature activity (full conversion) is observed for this catalyst for CO oxidation reaction compared to Au@SiO2 catalyst. A combination of optimum sized gold nanoparticles with a large amount of oxygen vacancies created due to Ti incorporation in silica matrix is considered to be the reason for this enhanced catalytic activity. The size of.gold nanoparticles is maintained even after high temperature pretreatments, which show the benefit of encapsulation. The effect of the various pretreatments on the catalytic activity has also been reported.

One pot ligand exchange method for a highly stable Au-SBA-15 catalyst and its room temperature CO oxidation - Soni, Yogita; Kavya, I.; Ajithkumar, T. G.; Vinod, C. P. (Chemical Communications, 2018)
A modified deposition precipitation (DP) method has been developed to address a fundamental issue of supporting well dispersed Au nanoparticles on silica. Ammonium chloride (NH4Cl) plays an important role in in situ modifying the gold precursor (HAuCl(4)3H(2)O) solution allowing facile deposition of gold NPs in the channels of SBA-15. The Au-SBA-15 catalyst (2.8 wt%) synthesized by this procedure showed 100% conversion for CO oxidation at room temperature with excellent stability at room temperature and high temperature.

Spectroscopic evidences for the size dependent generation of pd species responsible for the low temperature CO oxidation activity on Pd-SBA-15 nanocatalyst - Soni, Yogita; Pradhan, Sumanta; Bamnia, Mahesh K.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.; Khan, Tuhin Suvra; Haider, M. A.; Vinod, C. P. (Applied Catalysis B-Environmental, 2020)
A comprehensive size dependent CO oxidation activity has been demonstrated for Pd-SBA-15 catalysts with Pd NPs of varying sizes such as 1-2, 4-6 and 7-10 nm. Pd-SBA-15 catalyst with smallest sized NPs (Pd-S-N) has been synthesized by modified deposition precipitation method recently developed in our lab. Pd-S-N catalyst (reduced at 400 degrees C) demonstrated CO oxidation activity with lower light off temperature (50 degrees C), clearly one of the best reported for a Pd-silica system. A detailed XPS and in-situ DRIFTS analyses further supported by XAS and DFT calculations reveal the presence of easily decomposable highvalent Pd-oxide on co-ordinatively unsaturated Pd sites (Pdcus). Weak binding of CO on Pdcus sites in small Pd NPs leaving sites for oxygen activation is attributed to the low temperature activity of Pd-S-N for CO oxidation.
Keywords: CO oxidation; high-valent Pd species; Pd nanoparticles; SBA-15; under coordinated Pd atoms

Role of metal-support interaction for atmospheric pressure CO2 hydrogenation over Pd/(Ti)-SBA-15 catalyst: effect of titanium composition on products selectivity - Soni, Yogita; Gupta, Sharad; Vinod, C. P. (Molecular Catalysis, 2021)
The potential role of metal-support interaction for tuning the product selectivity during atmospheric pressure CO2 hydrogenation has been demonstrated on Pd/(Ti)-SBA-15 catalyst. Highly dispersed Pd NPs on SBA-15 (Pd/ SBA-15) was synthesized and further modified with titanium of varying composition. Comparison of catalytic activity of Pd/Ti-SBA-15 with its counterparts (Pd/SBA-15 and Pd/TiO2) illustrated the significance of strong PdTi interface in this catalyst and its role in tuning the product selectivity of CO2 hydrogenation. The generation of an ample amount of oxygen vacancies in the Pd/Ti-SBA-15 catalyst with maximum metallic Pd sites in close vicinity of Ti is proposed to boost the CO2 hydrogenation activity.
Keywords: CO2 hydrogenation; Metal-support interaction; Modified deposition precipitation; oxygen vacancies; Titanosilicates

Ultra-small Pd nanoparticles on SBA-15: an efficient catalyst for one-pot reductive alkylation of nitrobenzene with size-dependent activity - Soni, Yogita; Philip, Milda C.; Vinod, Chathakudath P. (Topics in Catalysis, 2025)
One-pot reductive alkylation of nitrobenzene with alcohol is an important organic synthesis reaction to form 2 degrees amines. In the present work, we have demonstrated that Pd/SBA-15 can be an effective catalytic system for this reaction. We have designed ultra-small Pd nanoparticles supported on SBA-15 for the synthesis of secondary amine, N-ethylaniline, through one-pot reductive alkylation of nitrobenzene with ethanol under ambient conditions. Ethanol functions both as the alkylating agent and the solvent in this process. The reaction is driven by the simultaneous hydrogenation of nitrobenzene to aniline, dehydrogenation of ethanol to aldehyde, and condensation of aniline and acetaldehyde to form N-ethylaniline. The size of the Pd nanoparticles plays a decisive role in the product selectivity. The undercoordinated sites present on ultra-small Pd NPs can facilitate ethanol dehydrogenation to acetaldehyde, thereby enhancing the selectivity towards N-ethylaniline compared to larger Pd nanoparticles. We have also studied the effect of different mesoporous supports such as SBA-15, MCM-41, and KIT-6 on the N-ethylaniline selectivity and found that SBA-15 was most selective. We have demonstrated that by carefully designing the catalyst such as controlling the Pd NPs size to obtain the maximum quantity of undercoordinated sites and choosing suitable support, the aliphatic alcohols can also be used for reductive alkylation of nitrobenzene in one-pot with optimum yields of N-alkylaniline.
Keywords: KIT-6; MCM-41; Modified deposition precipitation; nitrobenzene; Pd nanoparticles; Reductive alkylation; SBA-15; secondary amines; Undercoordinated Pd sites